A fresh perspective on Maqasid Waqf and its implications on law and waqf economy - Mohammad, Mohammad Tahir Sabit Haji (2018)
Often researchers mention the purposes of waqf for which a donation is made for a cause or a group of beneficiaries, such as building mosques, creating graveyards, schools, and feeding the hungry, etc. Recently Muslim thinkers have linked the Five Shari’ah Objectives to the waqf, which to an extent are helpful and enlightening. Other scholars have extended horizons further by introducing some fundament and general objectives of waqf that may affect various aspects of waqf, including law and regulation, governance, socioeconomic goals of Ummah and da’wah Islamiyah. These works need consolidation and further review, which will be offered in this paper.